The relationship between p53 expression, cell proliferation index and epidermal thickness in psoriasis - Sekar Djatiningrum, Sekar Djatiningrum (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: The specific process among psoriatic lesions is keratinocyte hyperproliferation state, and one of the genes that controls cell cycle is wild type of p53 gene. The correlation between p53 overexpression and psoriatic keratinocytes hyperproliferation has not been established yet. Objective: To clarify the relationship between p53 overexpression and psoriatic keratinocyte proliferation index, as well as the epidermal thickness resulted from this proliferation.Methods: 50 paraffin-embedded tissue sections were chosen from block collection of Pathologic Anatomy Department. The p53 overexpression was measured by counting the number of positive cell among 500 cell stained by antibody anti p53. The cell proliferation index was measured by counting the number of black dot among 100 epidermal cells stained by silver nitrate. The epidermal thickness, represented by the thickness of epidermal rete ridges was measured by using calibrated micrometer in hematoxillin stained section.Results: p53 expression was significantly correlated in fairly degree with cell proliferation index (r, = + 0,47; P < 0,001) and significantly correlated in moderately degree with epidermal thickness (r, = + 0,57; P < 0,001). Cell proliferation index was significantly correlated in fairly degree with epidermal thickness (r1 = + 0,37; P < 0,004).Keywords: psoriasis - p53 - cell proliferation index - Ag NOR - epidermal thickness